Ruling Ireland, 1685-1742 politics, politicians and parties - Hayton, David 1949- (Boydell & Brewer, 2004)
In a series of studies, David Hayton offers a comprehensive account of the government of Ireland during the period of transformation from 'New English' colonialism to Anglo-Irish 'patriotism', providing a chronological survey of the development of English policy towards Ireland and an account of the changing political structure of Ireland; particular attention is paid to the emergence of an English-style party system under Queen Anne. The Anglo-Irish dimension is also explored, through crises of high politics, and through an examination of the role played by Irish issues at Westminster. In his introduction Professor Hayton provides historical perspective, and establishes Irish political developments firmly in their British context. Professor D.W. HAYTON is Reader in Modern History at Queen's University, Belfast